DISCOVERY LEARNING DAN PEMAHAMAN KONSEPTUAL MATEMATIKA DI SEKOLAH DASAR: SYSTEMATIC REVIEW BUKTI EMPIRIS 2020–2025 - Muryaningrum, Shalis; Yan Dirk Wabiser; Lusia N. Amsad; Rian Efendi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Conceptual understanding is the foundation of learning mathematics in elementary school, but overly procedural teaching practices often lead students to memorize steps without understanding the meaning of concepts. This systematic review synthesizes empirical evidence on the effect of Discovery Learning on elementary students' mathematical conceptual understanding. The search was conducted through Google Scholar (2020–2025) using a stepwise strategy: (1) “discovery learning on conceptual understanding” (172 articles), (2) “discovery learning on mathematical conceptual understanding” (138 articles), and (3) “discovery learning on elementary students' mathematical conceptual understanding” (10 articles). Ten articles were analyzed using structured data extraction, design-based risk of bias assessment, and narrative synthesis. All studies reported improvements in conceptual understanding following the implementation of Discovery Learning, evidenced by increased pretest–posttest scores, differences between experimental and control groups, or higher mastery in classroom action research. However, the strength of evidence varied: most studies employed a single-group or classroom action research design (higher risk of bias), whereas quasi-experimental studies provided stronger support, although issues with initial ability equivalence remained. Practically, Discovery Learning is most promising when conducted as guided discovery, utilizing concrete–visual–symbolic representations, and tasks that encourage generalization. Further research requires more rigorous designs, reporting of effect sizes, and retention measurements.